Anomalous magnetic and dynamic behavior in magnetoresistive compounds: origin of bulk colossal magnetoresistivity: Дефекты в кристаллах - Chechersky, Vladimir; Nath, Amar (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
We present the results of our extensive Mössbauer effect studies carried out on a wide variety of mixed valence manganites as well as other types of magnetoresistive materials, includingpyrochlore Tl2Mn2O7 and the chalcospinels Fe0.5Cu0.5Cr2S4 and FeCr2S4 with absolutely different nature of magnetism, in a search for similarities linked to their magnetoresistive behavior. Double exchange electron transfer and coupling between the electrons and Jahn-Tellerlattice distortions invoked by most theories to explain colossal magnetoresistivity and associatedmetal-insulator transition in manganites are not applicable neither to pyrochlore nor to chalcospinels. Nevertheless, we find intriguing similarities in anomalous magnetic and dynamic behavior among these widely different systems at, above and below the Curie temperature TC, which shed light on the origin of bulk magnetoresistivity in general. All these compounds share the following features. The long range ferromagnetic order breaks down even below the Curie temperature with the formation of nano size spin clusters. Softening of latticewas observed near TC. The short range interactions in these spin clusters survive well above TC. When an external magnetic field is applied, the spin clusters coalesce to form large clusters with considerable lowering of resistivity. There is a strong evidence that the existence of nano size spin clusters with superparamagnetic-like behavior near TC is a prerequisite to occurrence of bulk magnetoresistity.